2013 IEEE 18th Conference on Emerging Technologies &Amp; Factory Automation (ETFA) 2013
DOI: 10.1109/etfa.2013.6647983
|View full text |Cite
|
Sign up to set email alerts
|

Benders/gossip methods for heterogeneous multi-vehicle routing problems

Abstract: In this paper, we propose a logic-based Benders decomposition (LBBD), as well as an LBBD/gossip method to solve the heterogeneous multi-vehicle routing problem (HMVRP). HMVRP is a newly formalized extension of the NP-hard multi-traveling salesman problem (mTSP). First, a hybrid algorithm based on LBBD is formulated that decomposes the HMVRP into an assignment problem and a cluster of sequencing problems. The former is solved by a mixed integer linear programming (MILP) solver, and the latter by a dedicated TSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The results of the Centralized method was used as a reference for comparing the results of the other algorithms. Riazi et al [2013] reported that the Centralized method was ineffective for problems with 14 tasks and beyond, mainly due to explosion of the sub-tour elimination constraints (SECs). However, in HHCRSP, we were able to solve instances as large as 35 tasks within a time limit of 2 hours.…”
Section: The Centralized Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the Centralized method was used as a reference for comparing the results of the other algorithms. Riazi et al [2013] reported that the Centralized method was ineffective for problems with 14 tasks and beyond, mainly due to explosion of the sub-tour elimination constraints (SECs). However, in HHCRSP, we were able to solve instances as large as 35 tasks within a time limit of 2 hours.…”
Section: The Centralized Methodsmentioning
confidence: 99%
“…In Riazi et al [2013], Logic-based Benders decomposition was used for the HMVRP to decompose the problem into a task assignment problem (master), and a series of scheduling subproblems in form of traveling salesman problems (TSPs). Integrating the Benders algorithm with a TSP solver for handling the subproblems led to significant speed ups that made the Benders method a viable alternative compared to the Centralized one.…”
Section: The Logic-based Benders Decompositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many results followed, for brevity's sake we mention the work by Ravazzi et al in [6] which characterized randomized affine dynamics with several applications to multi-agent systems, social networks and sensor networks and the very popular survey on gossip algorithms by Dimakis et al in [7] and references therein. We also mention applications of gossip algorithms proposed by Riazi et al to the heterogeneous multi-vehicle routing problem in [8] and to home healthcare scheduling problems [9].…”
Section: Introductionmentioning
confidence: 99%